2021
DOI: 10.1002/onco.13812
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adverse Events on Health Care Resource Utilization, Costs, and Mortality Among Patients Treated with Immune Checkpoint Inhibitors

Abstract: Background. We investigated the association between adverse events (AEs) suspected to be immune-related and health care resource utilization, costs, and mortality among patients receiving programmed cell death 1/programmed cell death ligand 1 immune checkpoint inhibitor (ICI) monotherapy for urothelial carcinoma, renal cell carcinoma, non-small cell lung cancer, or Merkel cell carcinoma. Patients and Methods. We conducted a retrospective cohort study using medical and pharmacy claims and enrollment information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The occurrence of AEs, including CSEs, following treatment with systemic therapy, has been associated with a decrease in HRQoL in patients with HCC [ 24 ]. Given the high cost of CSEs and their potential impact on patients’ HRQoL, patients with uHCC who are treated with systemic therapy should be frequently evaluated for CSEs to enable early detection [ 25 ]. This will enable more effective multidisciplinary management in order to improve patient outcomes and reduce the need for costly pharmacy services and inpatient stays [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of AEs, including CSEs, following treatment with systemic therapy, has been associated with a decrease in HRQoL in patients with HCC [ 24 ]. Given the high cost of CSEs and their potential impact on patients’ HRQoL, patients with uHCC who are treated with systemic therapy should be frequently evaluated for CSEs to enable early detection [ 25 ]. This will enable more effective multidisciplinary management in order to improve patient outcomes and reduce the need for costly pharmacy services and inpatient stays [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high cost of CSEs and their potential impact on patients’ HRQoL, patients with uHCC who are treated with systemic therapy should be frequently evaluated for CSEs to enable early detection [ 25 ]. This will enable more effective multidisciplinary management in order to improve patient outcomes and reduce the need for costly pharmacy services and inpatient stays [ 25 ]. A previous study demonstrated that experience in the management of sorafenib-related AEs can prolong survival and treatment duration in patients with HCC, highlighting the importance of effective AE management in this setting [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with urothelial carcinoma, renal cell carcinoma, non-small cell lung cancer (NSCLC) or Merkel cell carcinoma receiving immune checkpoint inhibitor therapy and experiencing treatment-related symptoms/AEs have an increased risk of unplanned hospitalisations and emergency room visits, and increased overall healthcare costs, compared with those without treatment-related symptoms/AEs. 7 In addition, the financial burden of using prescription medications and allied healthcare professionals (eg, physiotherapists, dieticians) to manage anticancer treatment-related symptoms/AEs can be a significant source of out-of-pocket patient expenses, which have not been well documented thus far. 8 Overall, there is a strong need for improved, patient-empowered management of cancer and anticancer treatment-related symptoms/AEs that may compromise improvements in patient outcomes or consume healthcare/financial resources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, treatment-related symptoms can be burdensome to patients, healthcare professionals and healthcare system resources. For instance, patients with urothelial carcinoma, renal cell carcinoma, non-small cell lung cancer (NSCLC) or Merkel cell carcinoma receiving immune checkpoint inhibitor therapy and experiencing treatment-related symptoms/AEs have an increased risk of unplanned hospitalisations and emergency room visits, and increased overall healthcare costs, compared with those without treatment-related symptoms/AEs 7. In addition, the financial burden of using prescription medications and allied healthcare professionals (eg, physiotherapists, dieticians) to manage anticancer treatment-related symptoms/AEs can be a significant source of out-of-pocket patient expenses, which have not been well documented thus far 8.…”
Section: Introductionmentioning
confidence: 99%